The bacterial community composition and its environmental drivers in the rivers around eutrophic Chaohu Lake, China - Shao, Keqiang (BMC Microbiol, 2021)
BACKGROUND: Bacterial community play a key role in environmental and ecological processes in river ecosystems. Rivers are used as receiving body for treated and untreated urban wastewaters that brings high loads of sewage and excrement bacteria. However, little is known about the bacterial community structure and functional files in the rivers around the eutrophic Chaohu Lake, the fifth largest freshwater lake in China, has been subjected to severe eutrophication and cyanobacterial blooms over the past few decades. Therefore, understanding the taxonomic and functional compositions of bacterial communities in the river will contribute to understanding aquatic microbial ecology. The main aims were to (1) examine the structure of bacterial communities and functional profiles in this system; (2) find the environmental factors of bacterial community variations. RESULTS: We studied 88 sites at rivers in the Chaohu Lake basin, and determined bacterial communities using Illumina Miseq sequencing of the 16 S rRNA gene, and predicted functional profiles using PICRUSt2. A total of 3,390,497 bacterial 16 S rRNA gene sequences were obtained, representing 17 phyla, and 424 genera; The dominant phyla present in all samples were Bacteroidetes (1.4-82.50 %), followed by Proteobacteria (12.6–97.30 %), Actinobacteria (0.1–17.20 %). Flavobacterium was the most numerous genera, and accounted for 0.12–80.34 % of assigned 16 S reads, followed by Acinetobacter (0.33–49.28 %). Other dominant bacterial genera including Massilia (0.06–25.40 %), Psychrobacter (0-36.23 %), Chryseobacterium (0.01–22.86 %), Brevundimonas (0.01–12.82 %), Pseudomonas (0-59.73 %), Duganella (0.08–23.37 %), Unidentified Micrococcaceae (0-8.49 %). The functional profiles of the bacterial populations indicated an relation with many human diseases, including infectious diseases. Overall results, using the β diversity measures, coupled with heatmap and RDA showed that there were spatial variations in the bacterial community composition at river sites, and Chemical oxygen demand (COD(Mn)) and (NH(4)(+) )were the dominant environmental drivers affecting the bacterial community variance. CONCLUSIONS: The high proportion of the opportunistic pathogens (Acinetobacter, Massilia, Brevundimonas) indicated that the discharge of sewage without adequate treatment into the rivers around Chaohu Lake. We propose that these bacteria could be more effective bioindicators for long-term sewage monitoring in eutrophic lakes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12866-021-02252-9.